Effector function and neutrophil cell death in the severity of sepsis with diabetes mellitus - Margalin, Brilliant; Arfijanto, Muhammad V.; Hadi, Usman (Narra Sains Indonesia, 2024)
Sepsis, a life-threatening condition resulting from immune dysregulation, is typically triggered by bacterial infections and commonly coexists with diabetes mellitus. Neutrophils are the first responders to infection and require regulated activation to control pathogen and damage-associated molecular patterns. Dysregulation of neutrophil activation leads to uncontrolled inflammatory responses, often observed in both sepsis and diabetes patients. Neutrophil dysregulation, characterized by effector dysfunction and inadequate cell death processes, can serve as a biomarker for assessing sepsis severity, particularly in diabetic patients. This review article provides information on the relationship between effector function, neutrophil cell death, and the severity of sepsis in individuals with diabetes mellitus, aiming to shed light on the mechanisms underlying sepsis progression. Topics covered in the review include an overview of effector function of neutrophil cells, mechanisms of neutrophil cell death, and dysregulation of effectors and neutrophil cell death processes in sepsis severity with diabetes mellitus.